MODERN METHOD OF FLOUR`S QUALITY CONTROL WITH THE HELP OF «INFRANEO» [Text] - Zhazykbayeva, G.M.; Aitkulov, N.N. (Science and education №4, 2018)
The modern economy demands not only productions of flour, various on food advantages, but also gaining the market since it is an important factor of stability of the enterprise in competition. Therefore on each mill it is necessary to develop several grades of flour especially as it is allowed by the modern legislation. The considered method of assessment of quality of flour by means of INFRANEO can be used at justification of use by production of flour according to requirements of standard documentation. Analyzing, the obtained data during the researches it is possible to draw the following conclusions: what flour «House», «Extra», the «Classic» is recommended to use as a premium flour on indicators whiteness and ashes. For improvement of sale it is recommended to expand the range of flour of the Premium class and to make packing on 2 and 5 kg. Современная экономика требует не только производства различной по пищевым достоинствам муки, но и завоевания рынка, т.к. это является важным фактором устойчивости предприятия в конкурентной борьбе. Поэтому на каждой мельнице следует вырабатывать несколько сортов муки, тем более, что это допускается современным законодательством. Рассматриваемый метод оценки качества муки с помощью ИНФРАНЕО можно использовать при обосновании использования при производстве муки в соответствии с требованиями нормативной документации. Анализируя, полученные данные в ходе исследований можно сделать следующие выводы: что муку «Домашняя», «Экстра», «Классик» рекомендуется использовать как примум мука по показателям белизна и золы. Для улучшения сбыта рекомендется расширить ассортимент муки Премиум класса и производить фасовку по 2 и 5 кг.
Keywords: рк; научный журнал; отечественное издание; периодическое издание; производство муки; качество муки; flour; gluten; protein; desiccant ability